Media Ajar PPKn Berbasis Perilaku Organisasi Dengan Menggunakan Karakter Doraemon di Sekolah Dasar - Ridwan Ardi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Pancasila and Citizenship Education (PPKn) in elementary schools plays a crucial role in shaping students' character, democratic attitudes, and social responsibility. However, PPKn learning is often considered monotonous due to the use of conventional, less engaging methods. This literature study aims to analyze the development of PPKn teaching media based on organizational behavior with an innovative approach using the Doraemon character as a visual aid. Doraemon was chosen because of its closeness to children's world, thus attracting attention and facilitating the internalization of organizational behavior values, such as cooperation, leadership, discipline, and responsibility. The research method used is a literature study by reviewing various previous research results related to popular character-based learning media, PPKn learning, and the application of organizational behavior concepts in elementary education. The results of the study indicate that teaching media with the integration of popular characters can increase learning motivation, strengthen the understanding of abstract concepts, and instill character values ​​through a fun approach. In addition, the contextual use of the Doraemon character encourages students to be more active in class discussions, fosters social skills, and builds collective awareness in solving problems together. This study concludes that the development of organizational behavior-based PPKn teaching media using the Doraemon character is a potential innovation for improving learning effectiveness and shaping the character of elementary school students in accordance with national education goals.